The boundary integral numerical modelling of the D.C. geoelectric field in a two-layered earth with a 3-D block inhomogeneity bounded by sloped faces - HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2021)
The paper presents an algorithm and numerical results for the boundary integral (B.I.E.) method of the forward D.C. geoelectric problem for a two-layered earth which contains a 3-D block inhomogeneity in the superficial layer. In comparison with previous numerical calculation the is algorithm is presented for the calculation of the boundary integrals for the cases with sloped planar boundary faces of the prism. Although the numerical calculations are more complicated in comparison with faces orthogonal to some of the x, y, z axis, this generalization to the sloped faces enables the treatment of the anomalous fields for the bodies of more general shapes than rectangular prisms. The graphs with numerical results present isoline maps of the potential, electric field components as well as the dipole profiling apparent resistivities when the source is the pair of D.C. electrodes at the surface of the earth.